UTILIZATION OF DIGITAL AND NON-DIGITAL LEARNING MEDIA IN IMPROVING FOREIGN LANGUAGE SKILLS - Husna, Ilya; Refdianti, Afrina; Afwan, Afwan; Rahmawati, Rahmawati; Azkiya, Hidayati (Edukasi: Jurnal Pendidikan, 2024)
This study aims to reveal digital and non-digital based learning media used by lecturers to improve 4 students' language skills in intensive Arabic learning UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan. The research method uses a qualitative descriptive approach. Data collection is obtained through observation, interviews, questionnaires, and documentation. The data is then analyzed using Miles and Huberman's theory: reduce the data, then present the data and then infer it. The research produced findings on the use of digital and non-digital based media in intensive Arabic language learning to improve Arabic language skills students of UIN Syahada Padangsidimpuan consists of several types based on the purpose of their use. The use of digital media can be grouped into 4 types based on the purpose of use, it's just that its use in Arabic language learning has not been too optimal due to several factors both in terms of students, lecturers, and institutional conditions. However, the combination of the use of digital and non-digital media in Arabic language learning can provide a balanced learning experience and maximize student learning outcomes and can improve students' Arabic language skills.